Developing a collaborative learning environment using a web-based design - Neo, M. (2003)
Today, technology is being used to support teachers in designing interesting and stimulating learning environments for students. In this paper, a web-based design project is used to create a collaborative learning environment with the aim of inculcating collaborative skills into the learners and increasing their problem-solving and critical thinking skills. The design project was created using multimedia tools such as Dreamweaver and Adobe-Photoshop. Students worked in groups and were actively responsible for their own learning processes. Results showed that students engaged in collaborative learning enhanced their problem-solving and critical thinking skills, learned to work in a team and became more autonomous learners.